Methodology of uniform contract law: the UNIDROIT principles in international legal doctrine and practice - Heidemann, Maren (2005)
Despite ever growing international trade and dispute settlement, a consistent international methodology of uniform private law has yet to be formed. This is needed in order to encourage the use of existing uniform transnational law rules specifically designed for application to international commercial contracts.